WGS to determine the extent of Clostridioides difficile transmission in a high incidence setting in North Wales in 2015. (15th December 2018) - Eyre, David W; Shaw, Robert; Adams, Helen; Cooper, Tracey; Crook, Derrick W; Griffin, Rhonda-Marie; Mannion, Phil; Morgan, Mari; Morris, Trefor; Perry, Michael; Jones, Sophie; Peto, Tim E A; et al.
Abstract: Objectives: Rates of Clostridioides ( Clostridium ) difficile infection (CDI) are higher in North Wales than elsewhere in the UK. We used WGS to investigate if this is due to increased healthcare-associated transmission from other cases. Methods: Healthcare and community C. difficile isolates from patients across North Wales (February–July 2015) from glutamate dehydrogenase (GDH)-positive faecal samples underwent WGS. Data from patient records, hospital management systems and national antimicrobial use surveillance were used. Results: Of the 499 GDH-positive samples, 338 (68%) were sequenced and 299 distinct infections/colonizations were identified, 229/299 (77%) with toxin genes. Only 39/229 (17%) toxigenic isolates were related within ≤2 SNPs to ≥1 infections/colonizations from a previously sampled patient, i.e. demonstrated evidence of possible transmission. Independent predictors of possible transmission included healthcare exposure in the last 12 weeks ( P = 0.002, with rates varying by hospital), infection with MLST types ST-1 (ribotype 027) and ST-11 (predominantly ribotype 078) compared with all other toxigenic STs ( P < 0.001), and cephalosporin exposure in the potential transmission recipient ( P = 0.02). Adjusting for all these factors, there was no additional effect of ward workload ( P = 0.54) or failure to meet cleaning targets ( P = 0.25). Use of antimicrobials is higher in North Wales compared with England and the rest of Wales. Conclusions: Levels of transmission detected by WGS were comparable to previously described rates in endemic settings; other explanations, such as variations in antimicrobial use, are required to explain the high levels of CDI. Cephalosporins are a risk factor for infection with C. difficile from another infected or colonized case.